Unraveling the conceptual ambiguity of digital human resource management: a state-of-the-art review - Sumbol Fiaz; Muhammad Azeem Qureshi (Cogent Social Sciences, 2024)
Digitalization is the fundamental aspect of the technological revolution that has introduced organizations to disruptive change. Not only external, but digitalization has also transformed all the internal mechanisms of organizations. The digital transformation of human resource management has been identified as a novel phenomenon. Therefore, during the past three decades, academicians have paid remarkable attention to and investigated the integration of technology with human resource management. Researchers strived to define this phenomenon in various ways and represent it with multiple terms. Interchangeable terms and different definitions have created ambiguity, and as a result, literature still lacks conceptual clarity. To address this gap, this study conducted a state-of-the-art review by following the six – step approach. The objective of this review is to clarify the conceptual ambiguity. This study employed Scopus, Web of Science and Google Scholar to identify relevant studies. A total of 1,274 articles were reviewed until finally 19 articles were identified as the subject of research. Firstly, this study presents the chronological development of the concept. Secondly, this study has analyzed the definitions of digital human resource management and its related concepts to identify the ambiguity that is misleading the literature in different directions. Through analysis this study explained the misunderstandings among different terms and concepts. The findings of this study have shown that digital HRM is a process of integrating human activities with advanced technology. Lastly, this study suggested an area for future research to further explore this evolving field.